PENGARUH DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PERUSAHAAN CHAROEN POKPHAND INDONESIA - Tiur Manurung, Elizabeth; Dhafin, Fadhlan; Riffat Arrazi, Muhammad (Universitas Muhammadiyah Metro, 2025)
This study aims to examine the effect of Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Charoen Pokphand Indonesia Tbk (CPIN) as part of the company's financial performance analysis. Based on the company's financial statement data from 2022 to 2024 analyzed by simple linear regression using IBM SPSS, it was found that DER had no significant effect on ROA. This shows that although the capital structure consisting of debt and equity can influence the company's financial decisions, its effect on profitability through asset efficiency is not proven to be significant. This study contributes to understanding the relationship between capital structure and firm profitability, and suggests financial managers to focus more on operational efficiency rather than relying solely on changes in funding structure to improve financial performance.